Oral manifestations of inflammatory bowel disease: the neglected piece of the puzzle. Issue 11 (November 2020) - Sbeit, Wisam; Kadah, Anas; Mahamid, Mahmud; Karayanni, Hala; Mari, Amir; Tali, Shani; Srouji, Samer; Khoury, Tawfik
Abstract : Inflammatory bowel disease (IBD) is a chronic relapsing remitting autoimmune disease including Crohn's disease and ulcerative colitis. IBD is associated with various extra-intestinal manifestations including oral manifestation. To date, only limited studies addressing the characteristics of the oral manifestations are available. The aim of the present review is to report the oral manifestations and their characteristics in IBD. A Medline/PubMed and Embase databases search were conducted and all relevant studies were extracted and analyzed. Overall, the oral manifestations in IBD were mostly associated with Crohn's disease rather than Ulcerative colitis where their prevalence ranged from 8 to 50%. Specific lesions for Crohn's disease include mucosal tags, cobblestoning and deep linear ulcerations with vertical fissures, while for ulcerative colitis, pyostomatisis vegetans was more disease specific. Notably, most of the oral manifestations were unrelated to disease activity, however more data are needed to accurately assess this correlation. Oral manifestations among IBD patients are not uncommon as Crohn's disease account for most of them. More data are warranted to precisely characterize their prevalence and association to intestinal activity.